The Effects of Family Ownership and Good Corporate Governance on Related Party Transactions - Tanaya, Tanaya; Ariefania, Maretta (Universitas Prasetiya Mulya, 2025)
This study investigates the impact of family ownership, independent commissioners, and ultimate beneficiary ownership (UBO) disclosure on non-business-related party transactions (RPTs) in Indonesian publicly listed firms. Using a sample of 351 firms from the Indonesian Stock Exchange between 2017 and 2022, we find that family-owned firms engage more extensively in non-business RPTs, suggesting potential expropriation risks. The presence of independent commissioners is found to be not significant in mitigating the non-business RPTs whilst UBO disclosure evidently mitigates such transactions, highlighting the governance role of transparency. Additionally, we explore whether economic crises—proxied by the COVID-19 pandemic—increase non-business RPTs. Our analysis reveals a decrease in significance related to the pandemic on the use of non-business RPTs by family-owned businesses through subsample tests. These findings contribute to the literature on corporate governance and RPTs, particularly in emerging markets with concentrated ownership structures.